BRCA1/2 Sequence Variants of Uncertain Significance: A Primer for Providers to Assist in Discussions and in Medical Management - Lindor, Noralane M. (AlphaMed Press, 2013)
INTRODUCTION. DNA variants of uncertain significance (VUS) are common outcomes of clinical genetic testing for susceptibility to cancer. A statistically rigorous model that provides a pathogenicity score for each variant has been developed to aid in the clinical management of patients undergoing genetic testing. METHODS. The information in this article is derived from multiple publications on VUS in BRCA genes, distilled for communicating with clinicians who may encounter VUS in their practice. RESULTS. The posterior probability scores for BRCA1 or BRCA2 VUS, calculated from a multifactorial likelihood model, are explained, and links for looking up specific VUS are provided. The International Agency on Cancer Research (IARC) of the World Health Organization has proposed a simple five-tier system for clinical management that is not widely known to clinicians. Classes 1 and 2 in this system are managed as neutral variants, classes 4 and 5 are managed as pathogenic variants, and class 3 variants still have insufficient evidence to move to either end of this scale and, thus, cannot be used in medical management. CONCLUSIONS. Development of models that integrate multiple independent lines of evidence has allowed classification of a growing number of VUS in the BRCA1 and BRCA2 genes. The pathogenicity score that is generated by this model maps to the IARC system for clinical management, which will assist clinicians in the medical management of those patients who obtain a VUS result upon testing.